(untitled) (LIS TODAY, 2024)
The prime objective of the present study is to analyze the impact of open-access publishing on research publications in data visualization journal research papers using scientometric indicators and science mapping techniques. A total of 9,018 publication records were extracted from the Scopus database for five years, from 2018 to 2022. The parameters used for the present study are open-access publication trends and their impact on the number of publications and citations, most prolific authors, organizations, countries, journals, etc. The study results indicate that 60.55% of articles on data visualization were published as open access, and the trend of open-access publication has grown exponentially. The study further found that open-access articles have a better academic impact than overall articles published. Huamin Qu of Hong Kong University of Science and Technology has contributed the highest number (22) of open-access articles on data visualization; the authors affiliated with the Centre National de la Recherche Scientifique (CNRS), Paris, have contributed the highest (116) OA articles; and the United States was the topmost productive country with the highest (1,809) OA articles. IEEE Transactions on Visualization and Computer Graphics was the most preferred journal among researchers on data visualization to publish their research as open-access articles.